A Survey on Demonstrating Patterns of Apis dorsata Colonization in Sariska Tiger Reserve, Rajasthan - Bhardwaj, Gobindsagar; Selvi, Gogul; Agasti, Saket; Singh, Hemant; Kumar, Anand; Reddy, G. V. (Indian Forester, 2020)
A pattern of honey bee colonization in Sariska Tiger Reserve (STR), Rajasthan, India was analyzed. Based on the observation of 242 bee colonies from the study areas, Ficus benghalensis. Ficus religiosa and Ficus glomerata are the most preferred tree species for colonization. Nearly 80% of bee colonies found on trees that are over 100cm in girth at girth breast height (gbh). This highlights the importance of large old trees for colonization. Similarly the bee colonies were most frequent in dense forest areas where less encounter of anthropogenic effects when compared to the degraded and agriculture fields/human settlement areas. We suggest periodical status survey of bee colonies both only in protected areas but also in other reserve forests.